Persepsi Masyarakat Lokal Terhadap Ruang Terbuka Hijau Pada Kota Berbasis Sungai - Hanny Maria Caesarina; Dienny Redha Rahmani (Universitas Lambung Mangkurat, 2020)
Banjarmasin is dominated with the combination of land and river, which resulted many riverside areas in the city. These areas are functioned as settlements area, as well as commercial and public areas as the focus of the city’s development and the local’s daily activities. However, the rapid development in Banjarmasin still giving less attention to the development of green open spaces, despite the local connection with the river. Therefore, this research aimed to identify the local perception of green open space in the riverside areas of Banjarmasin through descriptive qualitative analysis. Questionnaires and observations in five study areas were done to obtain the local perception. The results show that the highest local perception index is for the social aspects for 87,2 points and the lowest local perception index is the spatial planning aspects for 42,6 points. Banjarmasin needs to focus more on the spatial planning of green open spaces in riverside areas and enhancing the opportunity for locals to participate in any spatial planning process (participatory planning).